Comovement, information production, and the business cycle☆ - Brockman, Paul; Liebenberg, Ivonne; Schutte, Maria (Journal of Financial Economics, 2010)
Recent theoretical research suggests that information production is a positive externality of aggregate economic activity (Veldkamp, 2005). Both the quantity and quality of information increase during periods of economic expansion and decrease during periods of contraction. Based on this insight, we hypothesize and confirm that time-varying information production drives the comovement patterns observed in stock returns. We examine stock return comovement in 36 countries from 1980 to 2007 and show that, consistent with the theory, comovement patterns are countercyclical; that is, when information production is high (low), comovement is low (high). We also find that the relation between comovement and the business cycle is stronger in countries that experience large intertemporal swings in information production. Finally, we show that the relation between business cycle and comovement is stronger in poor countries, countries with less developed financial markets, and countries with weaker accounting and transparency standards. These results suggest that financial development and transparency are conducive to a steady flow of financial information over the business cycle.